165k views
5 votes
2−2s=4/3 s+13 how do you do this

User Xywang
by
5.8k points

1 Answer

6 votes

Answer: s = -3.3

Explanation:


2-2s=(4)/(3)s+13\\\\\\\underline{\text{Multiply everything by 3 to clear the denominator:}}\\(3)2-(3)2s=(3)(4)/(3)s+(3)13\\\\.\qquad 6-6s=4s+39\\\\\\\underline{\text{Add 6s to both sides:}}\\.\qquad 6-6s+6s=4s+6s+39\\\\.\qquad \qquad \qquad 6=10s+39\\\\\\\underline{\text{Subtract 39 from both sides:}}\\.\qquad \qquad 6-39=10s+39-39\\\\.\qquad \quad \quad -33=10s\\\\\\\underline{\text{Divide both sides by 10:}}\\.\qquad \quad \quad (-33)/(10)=(10s)/(10)

-3.3 = s

User Anshul Verma
by
4.8k points